2017
DOI: 10.1111/febs.14341
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and molecular mechanism of four‐electron reducing ferredoxin‐dependent bilin reductases from oceanic phages

Abstract: Suggested EC number for PcyX: 1.3.7.6 DATABASES: The PcyX X-ray structure was deposited in the PDB with the accession code 5OWG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…For many years, our laboratory has been interested in the biosynthesis of these open‐chain tetrapyrrole pigments and we have mostly concentrated on the biosynthesis of the pink pigment PEB . The biosynthesis of PEB starts with the heme oxygenase reaction, in which heme is cleaved at the α‐meso carbon to produce biliverdin IXα (BV) with the concomitantly liberation of carbon monoxide and ferric iron .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many years, our laboratory has been interested in the biosynthesis of these open‐chain tetrapyrrole pigments and we have mostly concentrated on the biosynthesis of the pink pigment PEB . The biosynthesis of PEB starts with the heme oxygenase reaction, in which heme is cleaved at the α‐meso carbon to produce biliverdin IXα (BV) with the concomitantly liberation of carbon monoxide and ferric iron .…”
Section: Introductionmentioning
confidence: 99%
“…Although PebA and PebS share a high structural similarity, the reaction of PebA is terminated directly after DHBV formation, whereas PebS proceeds further to produce PEB via the intermediate DHBV . PcyX on the other hand, although catalyzing formally the same reaction, does this by a different catalytic mechanism .…”
Section: Introductionmentioning
confidence: 99%
“…Some other genes reported in Cyanophage genomes 31 were detected in phages reported here. Two genes found in both Cyanophages and Cyanobacteria from global ocean habitats 32 , a heme oxygenase ( ho1 ) and a pcyX -like phycocyanobilin:ferredoxin oxidoreductase are involved in the production of phycobiliprotein pigment 32,33 . The ho1 and pcyX -like genes are adjacent in TP6_1, BML_S_1 and CB_1 and one-gene-apart in CB_2 ( Supplementary Fig.…”
Section: Metabolic Potentials Of Pmoc-phages and Their Relativesmentioning
confidence: 99%
“…The Prochlorococcus P-SSM2 phage Fd (pssm2-Fd) supports the reduction of phage phycoerythrobilin synthase (PebS), which catalyzes the reduction of biliverdin IXα to 3E/3Z phycoerythrobilin (27,28). While prior studies showed that some Fds support ET to diverse partner oxidoreductases (29)(30)(31)(32), it remains unclear how the biophysical properties of this and other phage Fds compare to host Fds, which can function as ET hubs that couple light harvesting to a range of reductive metabolic reactions (31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%